2019
DOI: 10.1038/s41598-019-53176-4
|View full text |Cite
|
Sign up to set email alerts
|

DDR1 autophosphorylation is a result of aggregation into dense clusters

Abstract: The collagen receptor DDR1 is a receptor tyrosine kinase that promotes progression of a wide range of human disorders. Little is known about how ligand binding triggers DDR1 kinase activity. We previously reported that collagen induces DDR1 activation through lateral dimer association and phosphorylation between dimers, a process that requires specific transmembrane association. Here we demonstrate ligand-induced DDR1 clustering by widefield and super-resolution imaging and provide evidence for a mechanism whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…This interface was reported to influence the rate of receptor endocytosis. These findings suggest that a signalling-competent RET ECD conformation is likely to involve higher order multimers consistent with findings for other RTKs such as EphR (Seiradake et al, 2010) EGFR (Needham et al, 2016) and DDR1 (Corcoran et al, 2019) RTKs. Therefore, a crucial aspect of receptor activation beyond the positioning of the RET transmembrane regions within a dimeric assembly is their arrangement within higher order clusters.…”
Section: Discussionsupporting
confidence: 86%
“…This interface was reported to influence the rate of receptor endocytosis. These findings suggest that a signalling-competent RET ECD conformation is likely to involve higher order multimers consistent with findings for other RTKs such as EphR (Seiradake et al, 2010) EGFR (Needham et al, 2016) and DDR1 (Corcoran et al, 2019) RTKs. Therefore, a crucial aspect of receptor activation beyond the positioning of the RET transmembrane regions within a dimeric assembly is their arrangement within higher order clusters.…”
Section: Discussionsupporting
confidence: 86%
“…Recently we and others identified a link between collagen-induced DDR1 clustering and the activation of the cytoplasmic kinase domain of DDR1 by phosphorylation of tyrosine 792 (Y792). This process then leads to phosphorylation of Y513 in neighboring dimers [ 9 , 10 ]. We found that cells expressing kinase-depleted DDR1d, or cells expressing kinase-dead DDR1e, or cells expressing DDR1b but cultured on non-activating fibronectin substrates, formed fewer and smaller clusters compared with cells expressing full-length kinase active DDR1b that were cultured on collagen.…”
Section: Introductionmentioning
confidence: 99%
“…We considered that collagen-induced DDR1 clustering induces DDR1 activation. This activation reinforces DDR1 binding to collagen that may involve a feedforward mechanism that increases receptor clustering [ 10 ]. Initial DDR1 clustering is not sufficient for DDR1 activation and DDR1 kinase activity is only triggered when DDR1 aggregates into dense clusters [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DDR-dependent signalling is not initiated at the level of dimers, but rather upon formation of higher-order clusters; here, receptor activation can occur through interactions between neighbouring dimers. Using fluorescent imaging, she recently obtained evidence that ligandinduced DDR1 phosphorylation results from aggregation into dense signalling clusters (Juskaite et al, 2017;Corcoran et al, 2019) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%